Accuracy of Tubal Patency Assessment during Office Hysteroscopy in Comparison to Hysterosalpingography - Nessyah Fatahan; Herbert Situmorang; Eka Rusdianto Gunardi; Muhammad Dwi Priangga (Indonesian Journal of Obstetrics and Gynecology, 2026)
AbstractObjective: To evaluate the accuracy of office hysteroscopy in assessing tubal patency compared with hysterosalpingography. Methods: This cross-sectional study was conducted from January 2021 to May 2023 and involved 26 subjects who underwent office hysteroscopy as part of a subfertility work-up. Tubal patency was assessed using the bubble test (Parryscope test) and by measuring changes in the amount of fluid in the pouch of Douglas after the procedure. All subjects subsequently underwent hysterosalpingography as the standard method. Due to technical limitations, diagnostic laparoscopy the gold standardwas not performed. Agreement between office hysteroscopy and hysterosalpingography was evaluated using concordance rates and kappa values, along with sensitivity, specificity, positive predictive value, and negative predictive value. Pain scores during the procedure and post-procedural symptoms were also analyzed. Results: The concordance between the two modalities in assessing tubal patency was 67% (moderate agreement), with a kappa value of 0.28 (fair agreement). Office hysteroscopy resulted in lower pain scores and a reduced incidence of post procedural lower back pain and abdominal bloating. Conclusion: Office hysteroscopy demonstrates fair accuracy in assessing tubal patency compared with hysterosalpingography, with the advantages of minimal pain and no serious side effects. Keywords: HSG, office hysteroscopy, tubal patency.